Students’ Competence in Cognitive Process and Knowledge in Biology Based on Curriculum Used in Indonesia - Paidi, Paidi; Mercuriani, Ixora Sartika; Subali, Bambang (International Journal of Instruction, 2020)
This research aim was to reveal the profile of competence in cognitive process and knowledge of grade 11 students of Indonesia's senior high school (SHS) on Biology in relation to the types of the curriculum implemented by the schools. The data were collected using test and self-report inventory technique. The research sample included 1,827 students spread across in five regions/districts of Indonesia. The data were analyzed descriptively using central-tendency and dispersion, and inferentially using independent sample t-test. The findings showed that the students' competence in cognitive process and knowledge in Biology subject is not satisfactory. With regards to the high-level cognitive process of analyzing, evaluating, and creating (C4, C5, and C6), there is a tendency that Curriculum 2013 is more effective than Curriculum 2006. Curriculum 2013 was also (tend to) more effective to develop the metacognitive knowledge especially for aspect of regulation of cognitive, Curriculum 2013 was also more effective than Curriculum 2006.